Flow enhancement using plant based polymer additives in brain-vessels-like microchannels - Heidarinik, Somaye (2019)
Plant based polymeric drag reduction additives (DRAs) obtained and extracted from natural resources started to gain interest and attention from scientists in an effort to replace the existing synthetic DRAs. The injection of a very small (Nano-molar) concentration of water soluble drag reducing polymers (DRPs) increases the blood circulation, tissue oxygenation and perfusion and decreases vascular resistance in animal models with no effect on blood vessels tone or viscosity. Furthermore, in microfluidic studies, it has been shown that the addition of DRPs will alter the distribution of red blood cells (RBC) in microcirculation. In this study, the effect of plant base DRAs on liquid flow enhancement through brain-vessels-like microchannels is investigated. The present work aims to study the feasibility of the natural polymer extracted from plant sources in enhancing the liquid flow in microchannels. Due to the development of microfluidics technology as an economical and reliable method for testing different theoretical phenomena related to engineering fields and medical fields, microchannel was utilized replacing the conventional method by using pipes which can reduce the usage of the chemical and reagents significantly. Plant base polymers were extracted from Okra, Aloe Vera and Hibiscus leaves using water extraction method. Different polymers solution concentrations were prepared by weight/weight basis after extraction by adding deionized (DI) water which acted as working fluid. Four microchannels which have a thickness about 200 µm with different clogging area simulating the human brain vessel size were fabricated using direct writing Lithography technique approach and then molded with polydimethylsiloxane (PDMS). The experiment was conducted using an open-loop microfluidic system. The flow enhancement performance of different concentration of the additives with different range of concentrations (100, 300, 500, 700 and 1000ppm) were evaluated by recording the flow rate corresponding to the operating pressure (50 to 500 mbar) for Okra, Aloe Vera and Hibiscus solutions. It is important to highlight that the examined plant base polymers have drag reduction properties. A non-linear relationship was obtained from this work between the concentration of the additives and percentage of flow rate increment (%FI). Increasing the polymer concentration increases the %FI until a limit which so-called critical concentration where beyond this point continuous increasing the concentration have an adverse effect on drag reduction. From the experimental results, Aloe Vera mucilage gives highest drag reduction performance (14.02%) by achieving higher %FI as Aloe Vera in lower concentrations (100, 300 and 500ppm) mucilage and Okra (13.5%) for higher concentrations (700 and 1000ppm). Moreover, Hibiscus showed the lowest %FI in this study (-15%). In most of the cases, increasing of the operating pressure up to the critical pressure of 400mbar, resulted in the increasing of %FI. The experimental results validate the potential use of these additives in medical fields to enhance the blood flow in semi-clogged blood streams which can be an alternative treatment for cardiovascular diseases. It was recommended that more new natural polymeric DRAs should be investigated and explored the possibility of these polymers to dissolve the cholesterol which cause narrowing of the blood vessels.